PENGARUH LATIHAN ALTERNATE LEG BOUND TERHADAP HASIL DAYA LEDAK OTOT TUNGKAI PADA SISWA KELAS XI SMAKF IKASARI PEKANBARU - Ramadhan, Ikwal; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Observations in the field and on the basis of statements made to the teacher who has authority during the learning activities, it is still said that Class XI SMK IKASARI Pekanbaru is weak in terms of his strength. This is apparent from the large number of students who are unable to reach the standards set by the teacher. In addition, rejecting students also saw that they looked slow, so that the results of the jump were short. The aim of this study was to determine: